Solovyov's Metaphysics between Gnosis and Theurgy - Gaisin, Aleksandr (2018)
This article provides a reading of Vladimir Solovyov's philosophy as expressed in his Lectures on Divine Humanity' and The Meaning of Love'. It seeks to unpack his eclectic thought in order to answer the question of whether there is a Jewish Kabbalistic influence on the Russian thinker amidst his usual platonic, gnostic, and Schellengian tropes. Interested as a young man in Jewish Mysticism, Solovyov fluctuates in his Lectures on Divine Humanity' between a platonic reading of Schellengian Gnosticism and some elements of Kabbalistic origin. In The Meaning of Love', he develops a notion of love that puts him very close to what Moshe Idel calls theosophic-theurgical Kabbalah'. Showing how The Meaning of Love' completes the narrative of Lectures', we can affirm that there is a certain Christian Kabbalistic line in Solovyov's thought that culminates in his theurgical understanding of love. In this sense, Solovyov might be called a philosophical Marrano as he is certainly a heterodox theosopher that fluctuates between Christian Gnosis and Christian Kabbalah, never assuming a solid identity.
Keywords: Christian Kabbalah; Judeo-Christianity; Russian Religious Renaissance; Vladimir Solovyov; Heterodoxy; Philosophical Theology